2018
DOI: 10.1002/hep4.1200
|View full text |Cite
|
Sign up to set email alerts
|

Gut and Liver B Cells of Common Clonal Origin in Primary Sclerosing Cholangitis–Inflammatory Bowel Disease

Abstract: B cells express an antigen‐specific B‐cell receptor (BCR) and may contribute to liver inflammation by recognizing shared antigens in the gut and liver. Herein, we used high‐throughput BCR sequencing of the immunoglobulin heavy chain, specifically the complementarity‐determining region 3 (CDR3), to characterize the B‐cell repertoire of freshly‐frozen paired gut and liver tissue samples from patients with primary sclerosing cholangitis (PSC) and concurrent inflammatory bowel disease (IBD) (PSC‐IBD, n = 10) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…B cell clonality studies also point to the involvement of as yet unidentified auto-antigens, with individuals with PSC exhibiting increased B cell clonality in the liver and gut compared to healthy tissue (123). This study also found significant overlap in expanded B cell clones shared between the gut and liver (123), further supporting the hypothesis that loss of tolerance in the gut is important.…”
Section: Autoantibodies and B Cell Clonality In Pscsupporting
confidence: 66%
See 1 more Smart Citation
“…B cell clonality studies also point to the involvement of as yet unidentified auto-antigens, with individuals with PSC exhibiting increased B cell clonality in the liver and gut compared to healthy tissue (123). This study also found significant overlap in expanded B cell clones shared between the gut and liver (123), further supporting the hypothesis that loss of tolerance in the gut is important.…”
Section: Autoantibodies and B Cell Clonality In Pscsupporting
confidence: 66%
“…Supernatants from liver infiltrating B cells isolated from PSC patients and cultured ex-vivo have been shown to react to several proteins in an array assays, including nucleolar protein 3 (NOD3), expressed by cholangiocytes (82). B cell clonality studies also point to the involvement of as yet unidentified auto-antigens, with individuals with PSC exhibiting increased B cell clonality in the liver and gut compared to healthy tissue (123). This study also found significant overlap in expanded B cell clones shared between the gut and liver (123), further supporting the hypothesis that loss of tolerance in the gut is important.…”
Section: Autoantibodies and B Cell Clonality In Pscmentioning
confidence: 99%
“…63,64 An important clue to the “gut–liver axis” hypothesis of PSC pathogenesis lies in the discovery of B cell clones within the liver and colonic tissue of PSC patients. 65 BCR sequencing revealed that 8.3% of B cell clones overlapped with paired colon and liver samples, suggesting that the same Ag(s) was driving B cell activation in both organs.…”
Section: Primary Sclerosing Cholangitismentioning
confidence: 99%
“…Although BAFF controls B cell maturation and survival, its high levels accompany chronic inflammation in the gut 80 . Antigen‐presenting cells that express B cell receptors (BCRs) constitute a major humoral component of the adaptive immune system 81 . A large number of B cells may infiltrate intestinal inflammatory sites, where they provide a response to recognized antigens through a broad spectrum of non‐specific antibodies 81 .…”
Section: B Cellsmentioning
confidence: 99%
“…Antigen‐presenting cells that express B cell receptors (BCRs) constitute a major humoral component of the adaptive immune system 81 . A large number of B cells may infiltrate intestinal inflammatory sites, where they provide a response to recognized antigens through a broad spectrum of non‐specific antibodies 81 . Both the BAFF pathway and TGF‐β–induced IgA class switching are mediated by RUNX3/RUNX1 cross‐regulation 12,82 .…”
Section: B Cellsmentioning
confidence: 99%